2021
DOI: 10.1016/j.critrevonc.2020.103189
|View full text |Cite
|
Sign up to set email alerts
|

Italian survey on the clinical management of non-small cell lung cancer patients during the COVID-19 pandemic: A lesson for the second wave

Abstract: This study investigated the clinical management of non small cell lung cancer (NSCLC) patients during the first wave of coronavirus disease 2019 (COVID-19) outbreak in Italy. A 29-questions survey was sent to 95 Italian thoracic oncologists, with 77 % of them declaring significant changes in the outpatients management and treatment. The results of this survey pointed out a significant delay of lung cancer diagnosis along with a relevant reduction of patients' accrual within clinical trials. Telemedicine emerge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…In addition, many studies have shown an important delay in cancer treatment that requires appropriate changes in treatment decisions [ 47 , 48 ]. During the pandemic, oncologists’ hot topic was to ensure the continuum of care: oncologic departments were substantially reorganized in the management and maintenance of life-saving treatments.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, many studies have shown an important delay in cancer treatment that requires appropriate changes in treatment decisions [ 47 , 48 ]. During the pandemic, oncologists’ hot topic was to ensure the continuum of care: oncologic departments were substantially reorganized in the management and maintenance of life-saving treatments.…”
Section: Discussionmentioning
confidence: 99%
“…This affected the delivery of standard care for patients with lung cancer. 21,[23][24][25][26][27] Lung cancer patients had decreased utilization of outpatient services, hospital admissions, and surgical procedures during the first months of the pandemic. 27 A large allocation of health resources towards caring for patients sick with COVID-19 made it more difficult for many institutions to maintain standard care.…”
Section: Discussionmentioning
confidence: 99%
“…Telemedicine helped in patienthealthcare interactions and in administering concurrent therapeutic regimes for managing lung cancer patients with COVID. 128 According to TERAVOLT registry, the first wave of COVID had profoundly affected the mortality rates of cancer patients with approximately 30% mortality being reported in thoracic malignancy cases. However, during the second wave, data from South Africa revealed a notable decrease in severity and mortality in lung cancer patients amidst the Omicron wave.…”
Section: Lung Cancermentioning
confidence: 99%